The NOTCH Pathway and Its Mutations in Mature B Cell Malignancies - Arruga, Francesca; Vaisitti, Tiziana; Deaglio, Silvia (Frontiers in Oncology, 2018)
The systematic application of next-generation sequencing to large cohorts of oncologic samples has opened a Pandora’s box full of known and novel genetic lesions implicated in different steps of cancer development and progression. Narrowing down to B cell malignancies, many previously unrecognized genes emerged as recurrently mutated. The challenge now is to determine how the mutation in a given gene affects the biology of the disease, paving the way to functional genomics studies. Mutations in NOTCH family members are shared by several disorders of the B series, even if with variable frequencies and mutational patterns. In silico predictions, revealed that mutations occurring in NOTCH receptors, despite being qualitatively different, may have similar effects on protein processing, ultimately leading to enhanced pathway activation. The discovery of mutations occurring also in downstream players, either potentiating positive signals or compromising negative regulators, indicates that multiple mechanisms in neoplastic B cells concur to activate NOTCH pathway. These findings are supported by results obtained in chronic lymphocytic leukemia and splenic marginal zone B cell lymphoma where deregulation of NOTCH signaling has been functionally characterized. The emerging picture confirms that NOTCH signaling is finely tuned in cell- and microenvironment-dependent ways. In B cell malignancies, it contributes to the regulation of proliferation, survival and migration. However, deeper biological studies are needed to pinpoint the contribution of NOTCH in the hierarchy of events driving B cells transformation, keeping in mind its role in normal B cells development. Because of its relevance in leukemia and lymphoma biology, the NOTCH pathway might represent an appealing therapeutic target: the next few years will tell whether this potential will be fulfilled.